2012
DOI: 10.3390/toxins4020055
|View full text |Cite
|
Sign up to set email alerts
|

Plant Ureases and Related Peptides: Understanding Their Entomotoxic Properties

Abstract: Recently, ureases were included in the arsenal of plant defense proteins, alongside many other proteins with biotechnological potential such as insecticides. Isoforms of Canavalia ensiformis urease (canatoxin—CNTX and jack bean urease—JBURE-I) are toxic to insects of different orders. This toxicity is due in part to the release of a 10 kDa peptide from the native protein, by cathepsin-like enzymes present in the insect digestive tract. The entomotoxic peptide, Jaburetox-2Ec, exhibits potent insecticidal activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 56 publications
0
30
0
Order By: Relevance
“…In previous studies, we reported that the lethality of Jack Bean ureases given orally to insects depends on characteristics of their digestive system (Stanisçuaski and Carlini, 2012). At least part of the insecticidal effect is caused by toxic peptides derived from ureases upon cleavage by insect's digestive enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous studies, we reported that the lethality of Jack Bean ureases given orally to insects depends on characteristics of their digestive system (Stanisçuaski and Carlini, 2012). At least part of the insecticidal effect is caused by toxic peptides derived from ureases upon cleavage by insect's digestive enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Although JBU has been proven to be insecticidal to different insects (Stanisçuaski and Carlini, 2012), it displayed no lethality in Nauphoeta cinerea cockroaches, at least not by intrabdominal administration in a 24 hours observation time. In previous studies, we reported that the lethality of Jack Bean ureases given orally to insects depends on characteristics of their digestive system (Stanisçuaski and Carlini, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the jackbean ureases, it has been demonstrated that this entomotoxic effect is a highly complex event, involving the intact protein as well as the release of a toxic peptide [82,89,90]. Jackbean ureases and their derived peptides affect several physiological processes in the insects, including the fluid transport across membranes [83,91,92]. So far, no studies regarding es-SBU mechanism of action in insects were performed, but it reasonable to assume that, due to their very similar sequences (92% of similarity), es-SBU and JBU would have the same targets in these organisms.…”
Section: New Features Of An Old Protein -Activities Unrelated To the mentioning
confidence: 99%